2014
DOI: 10.2323/jgam.60.270
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of alkaliphilic bacteria for production of high optically pure L-(+)-lactic acid

Abstract: Lactic acid bacteria that grow under alkaline conditions (pH 10) were isolated from various sources in Okinawa (Japan). These alkali-tolerant and alkaliphilic bacteria were classified as follows: Microbacterium sp. Key words: alkaliphilic bacteria; batch fermentation; Enterococcus casseliflavus; glucose; L-lactic acid Introduction L-Lactic acid is an important metabolite for industrial production of bioplastic materials, and the demand for its expansion in the future is highly expected. Though this optical iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
(16 reference statements)
0
13
0
2
Order By: Relevance
“…Except for an alkalophilic Bacillus sp. WL-S20 that produced 225g/l from glucose at a yield of 99.3g/g using multi-pulse Fed batch fermentation [7], the final LA concentration (140.8g/l) and LA yield (0.93-0.99g/g of glucose consumed) obtained in the current study under alkaliphilic condition using the green neutralizer (NaOH) to maintain the pH during fermentation were acceptable when compared with other wilD-type alkaliphilic strains e.g Halolactibacillus halophilus (65.8g/l L-LA with yield of 0.76g/g) [10], Exiguobacterium 8-11-1 (125g/l of L-LA with a yield of 0.98g/g) [12], Enterococcus casseliflavus 79w3 (103g/l of L-LA with yield of 0.80g/g) [13].…”
Section: Fed Batch Fermentationmentioning
confidence: 93%
See 1 more Smart Citation
“…Except for an alkalophilic Bacillus sp. WL-S20 that produced 225g/l from glucose at a yield of 99.3g/g using multi-pulse Fed batch fermentation [7], the final LA concentration (140.8g/l) and LA yield (0.93-0.99g/g of glucose consumed) obtained in the current study under alkaliphilic condition using the green neutralizer (NaOH) to maintain the pH during fermentation were acceptable when compared with other wilD-type alkaliphilic strains e.g Halolactibacillus halophilus (65.8g/l L-LA with yield of 0.76g/g) [10], Exiguobacterium 8-11-1 (125g/l of L-LA with a yield of 0.98g/g) [12], Enterococcus casseliflavus 79w3 (103g/l of L-LA with yield of 0.80g/g) [13].…”
Section: Fed Batch Fermentationmentioning
confidence: 93%
“…Alkaliphilic strains can also considered good producers for organic acids [11]. Very few alkaliphilic strains have been reported for LA production from glucose such as Halolactibacillus halophilus that produced 65.8g/l L-LA in batch fermentation at pH 9.0 with a low yield of 0.76g/g [10], Exiguobacterium 8-11-1 strain produced 125g/l of L-LA with a yield of 0.98g/g in Fed batch fermentation at pH 8.5 [12], Enterococcus casseliflavus 79w3 that produced 103g/l of L-LA with a low yield of 0.80g/g at pH 8.0 in batch fermentation [13] and genetically modified Bacillus N16-5 that produced 143.9g/l of D-LA with a yield of 96.1g/g of glucose consumed in Fed batch fermentation [14]. These studies either reported a low concentration of LA with low yield or performed at slightly alkaline conditions that increase the risk of contamination, in addition to the expected instability of genetically modified organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Mặc dù hàm lượng pyruvate của chủng ND7 cao hơn rất nhiều so với công bố trước đó của Ngô Thị Hoài Thu và nnk., (2018) (0,11 g/L) nhưng vẫn còn thấp để có thể sử dụng để sản xuất pyruvate ở quy mô lớn hơn. Nghiên cứu của Kawata et al (2016) Theo công bố của Calabia et al, (2011), Yokaryo & Tokiwa (2014) các chủng vi khuẩn có khả năng chịu kiềm là những chủng tiềm năng để sản xuất các axit hữu cơ trong đó có pyruvate. Kawata et al (2016) đã phát hiện khả năng pyruvate được tiết ra môi trường nuôi cấy lên tới 63,3 g/L sau 48 giờ nuôi chủng vi khuẩn Halomonas sp.…”
Section: Một Số đặC đIểm Hình Thái Hóa Sinh Của Các Chủng VI Khuẩn ưunclassified
“…Being naturally tolerant to salt and osmotic pressure, halophilic microbes have recently gained attention for microbial production of organic acids [45][46][47]. One alkaliphilic, halophilic Halomonas generated 63 g/L pyruvate in 48 h under aerobic conditions using an unsterilized defined medium having high ionic strength [48].…”
Section: Medium Optimizationmentioning
confidence: 99%